A Stretching Device for High Resolution Live-Cell Imaging - Huang, Lawrence (2010)
Several custom-built and commercially available devices are available to investigate cellular responses to substrate strain. However, analysis of structural dynamics by microscopy in living cells during stretch is not readily feasible. We describe a novel stretch device optimized for high-resolution live-cell imaging. The unit assembles onto standard inverted microscopes and applies constant magnitude or cyclic stretch at physiological magnitudes to cultured cells on elastic membranes. Interchangeable modular indenters enable delivery of equibiaxial and uniaxial stretch profiles. Strain analysis performed by tracking fluorescent microspheres adhered onto the substrate demonstrated reproducible application of stretch profiles. In endothelial cells transiently expressing EGFP-vimentin and paxillin-DsRed2 and subjected to constant magnitude equibiaxial stretch, the 2-D strain tensor demonstrated efficient transmission through the extracellular matrix and focal adhesions. Decreased transmission to the intermediate filament network was measured, and a heterogeneous spatial distribution of maximum stretch magnitude revealed discrete sites of strain focusing. Spatial correlation of vimentin and paxillin displacement vectors provided an estimate of the extent of mechanical coupling between the structures. Interestingly, switching the spatial profile of substrate strain reveals that actin-mediated edge ruffling is not desensitized to repeated mechano-stimulation. These initial observations show that the stretch device is compatible with live-cell microscopy and is a novel tool for measuring dynamic structural remodeling under mechanical strain.